Highlights on Practical Applications of Agents and Multi-Agent Systems International Workshops of PAAMS 2013, Salamanca, Spain, May 22-24, 2013. Proceedings - Corchado Rodríguez, Juan Manuel; Bajo Pérez, Javier; Kozlak, Jaroslaw; Pawlewski, Pawel; Molina, Jose M.; Julián, Vicente; Silveira, Ricardo Azambuja; Unland, Rainer; Giroux, Sylvain (Communications in Computer and Information Science,, 2013)
This book constitutes the refereed proceedings of the Workshops which complemented the 11th International Conference on Practical Applications of Agents and Multi-Agent Systems, PAAMS 2013, held in Salamanca, Spain, in May 2013. This volume presents the papers that have been accepted for the workshops: Workshop on Agent-based Approaches for the Transportation Modeling and Optimization, Workshop on Agent-Based Solutions for Manufacturing and Supply Chain, Workshop on User-Centric Technologies and Applications, Workshop on Conflict Resolution in Decision Making, Workshop on Multi-Agent System Based Learning Environments, Workshop on Multi-agent based Applications for Sustainable Energy Systems, Workshop on Agents and multi-agent Systems for AAL and e-Health.